2022
DOI: 10.1002/wps.20939
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a WHO self‐help psychological intervention for preventing mental disorders among Syrian refugees in Turkey: a randomized controlled trial

Abstract: Refugees are at high risk of developing mental disorders. There is no evidence from randomized controlled trials (RCTs) that psychological interventions can prevent the onset of mental disorders in this group. We assessed the effectiveness of a self‐help psychological intervention developed by the World Health Organization, called Self‐Help Plus, in preventing the development of mental disorders among Syrian refugees experiencing psychological distress in Turkey. A two‐arm, assessor‐masked RCT was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 36 publications
2
56
0
Order By: Relevance
“…Psychological distress poses risk for subsequent mental disorders and causes marked impairment, so a beneficial effect of SH + on psychological distress represents an important finding. A trial with a design similar to the present study conducted with refugees in Turkey found that participants allocated to SH + were significantly less likely to have any mental disorders after 6 months of follow-up compared to the control group (Acarturk et al ., 2022). Considering that both this study and the Turkish SH + study observed effects on key measures several months after the intervention, we hypothesise these findings may be related to the main SH + components which were delivered over the five weekly sessions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological distress poses risk for subsequent mental disorders and causes marked impairment, so a beneficial effect of SH + on psychological distress represents an important finding. A trial with a design similar to the present study conducted with refugees in Turkey found that participants allocated to SH + were significantly less likely to have any mental disorders after 6 months of follow-up compared to the control group (Acarturk et al ., 2022). Considering that both this study and the Turkish SH + study observed effects on key measures several months after the intervention, we hypothesise these findings may be related to the main SH + components which were delivered over the five weekly sessions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect was much more pronounced for the Turkey study where efficacy (i.e. reducing the frequency of any mental disorder) was observed at 6 months (Acarturk et al, 2022), compared to the Western European study where a preventative effect was only found immediate postintervention and not after 6 months (Purgato et al, 2021). In both studies, we planned a long-term follow-up at 12 months, but data at 12 months are only available for the Western European study due to logistic and administrative problems occurred in Turkey.…”
Section: Introductionmentioning
confidence: 94%
“…Clinical interventions focused on psychoeducation, psychosocial support and brief psychological therapies (including recent innovations, such as self-help plus40 41 and problem-management plus),42–46 all of which are recommended by the mhGAP-IG and associated resources. Similarly, interventions targeted depression, substance use and child and adolescent mental health conditions: all mhGAP-IG modules.…”
Section: Conclusion and Clinical Implicationsmentioning
confidence: 99%
“…Notably, a preventative effect on the development of mental disorders has recently been demonstrated for Self Help Plus (SH+), a WHO self-help psychological intervention that can be delivered to up to 30 people at once by briefly trained non-specialist facilitators (Epping-Jordan et al ., 2016; WHO, 2021 a ). Two randomised trials, one conducted in Western Europe and another in Turkey, have recently assessed the preventative effect of SH+ in refugee populations (Purgato et al ., 2021; Acarturk et al ., 2022), while a trial in Uganda showed its beneficial effects for reducing psychological distress (Tol et al ., 2020). Both the Western European and Turkey studies showed evidence of an effect of SH+ in preventing the onset of mental disorders and reducing stress, but differences were observed between the studies.…”
mentioning
confidence: 99%
“…The effect was much more pronounced for the Turkey study where efficacy (i.e. reducing the frequency of any mental disorder) was observed at 6 months, compared to the Western European study where beneficial effects were only found immediate post-intervention and not after six months (Purgato et al ., 2021; Acarturk et al ., 2022). As SH+ is a low-intensity, brief intervention, it cannot deal with the full range of difficulties that refugees and asylum seekers may experience following war-related traumatic events.…”
mentioning
confidence: 99%